Bacteria Associated With a Commercial Mycorrhizal Inoculum: Community Composition and Multifunctional Activity as Assessed by Illumina Sequencing and Culture-Dependent Tools - Agnolucci, Monica; Avio, Luciano; Pepe, Alessandra; Turrini, Alessandra; Cristani, Caterina; Bonini, Paolo; Cirino, Veronica; Colosimo, Fabrizio; Ruzzi, Maurizio; Giovannetti, Manuela (Frontiers in Plant Science, 2019)
The implementation of sustainable agriculture encompasses practices enhancing the activity of beneficial soil microorganisms, able to modulate biogeochemical soil cycles and to affect soil fertility. Among them, arbuscular mycorrhizal fungi (AMF) establish symbioses with the roots of most food crops and play a key role in nutrient uptake and plant protection from biotic and abiotic stresses. Such beneficial services, encompassing improved crop performances and soil resources availability, are the outcome of the synergistic action of AMF and the vast communities of mycorrhizospheric bacteria living strictly associated with their mycelium and spores, most of which showing plant growth promoting (PGP) activities, such as the ability to solubilize phosphate and produce siderophores and indole acetic acid (IAA). One of the strategies devised to exploit AMF benefits is represented by the inoculation of selected isolates, either as single species or in a mixture. Here, for the first time, the microbiota associated with a commercial AMF inoculum was identified and characterized, using a polyphasic approach, i.e. a combination of culture-dependent analyses and metagenomic sequencing. Overall, 276 bacterial genera were identified by Illumina high-throughput sequencing, belonging to 165 families, 107 orders and 23 phyla, mostly represented by Proteobacteria and Bacteroidetes. The commercial inoculum harboured a rich culturable heterotrophic bacterial community, whose populations ranged from 2.5 to 6.1 x 106 CFU/mL. The isolation of functional groups allowed the selection of 36 bacterial strains showing PGP activities. Among them, 14 strains showed strong IAA and/or siderophores production and were affiliated with Actinomycetales (Microbacterium trichotecenolyticum, Streptomyces deccanensis/scabiei), Bacillales (Bacillus litoralis, Bacillus megaterium), Enterobacteriales (Enterobacter), Rhizobiales (Rhizobium radiobacter). This work demonstrates for the first time that an AMF inoculum, obtained following industrial production processes, is home of a large and diverse community of bacteria with important functional PGP traits, possibly acting in synergy with AMF and providing additional services and benefits. Such bacteria, available in pure culture, could be utilized, individually and/or in multispecies consortia with AMF, as biofertilizers and bioenhancers in sustainable agroecosystems, aimed at minimizing the use of chemical fertilizers and pesticides, promoting primary production and maintaining soil health and fertility.